Firms' Involvement in Standardization and Average Total Costs per Patent Family - Yanis Gamarra; Gunther Friedl (International Telecommunications Society (ITS), 2022)
Technology standards such as the Wi-Fi or 5G mobile communication standard rely on standard-essential patents (SEPs). Increasing licensing revenues and several disputes between owners and users of SEPs raise the question about the patenting behavior of firms developing standardized technologies. A better understanding of this patenting behavior can help to improve the standard-setting process and standard adoption. We propose the average total costs per patent family as an economic assessment criterion and an indicator of patenting behavior for technology standards. Using this criterion, we examine how increasing SEP family portfolios and their ownership concentration are associated with firms' patenting behavior. We find that increasing ownership concentration of SEP families is negatively associated with firms' average total costs per patent family, suggesting that decreasing competition around SEP families might decrease firms' investments per patent family. We conclude that policy makers and standardsetting organizations (SSOs) should discourage blanket declarations since increasing SEP transparency could improve comparability across standard-setting processes and reduce uncertainties in subsequent standard adoption for SEP holders and implementers. SSOs should further closely monitor how increasing (decreasing) ownership concentration of SEPs affects their standard-setting processes.
Keywords: L15; L96; O32; O34; 330; Average total costs; standardization; standard-essential patents; patenting; R&D